KEPEMIMPINAN MUTU KEPALA SEKOLAH DALAM PENINGKATAN MUTU PENDIDIKAN - Herawan, Endang (Universitas Pendidikan Indonesia, 2014)
The headmaster of an educational leader has an important role in improving the quality. In line with the role that is so important given to schools, namely improving the quality of human resources, the school in carrying out its functions should be able to provide quality education services to the participants, because the leadership exercised by the principal should be oriented to the quality of leadership concerned .. primary on quality, so-called leadership qualities. Quality leadership is leadership that always wants something perfect or best. leadership quality is basically an effect process for quality improvement, where leaders try to influence Bahawan to do what is deemed important by the leader. Leadership that leads to quality includes three managerial functions, including planning, control, and improvement in quality. School principals are implementing quality leadership, will share the responsibility, continuous improvement, providing materials and tools are required of teachers and staff. In the leadership quality of each component involved in education is theleader, in which each person is responsible to eliminate the obstacles faced, which could hinder the successful implementation of the task.Keywords: Leadership, Quality , School Management